Social Disorganization Theory: The Role of Diversity in New Jersey's Hate Crimes - Ciobanu, Dana Maria (2016)
The reported number of hate crimes in New Jersey continues to remain high despite the enforcement of laws against perpetrators. The purpose of this correlational panel study was to test Shaw & McKay's theory of social disorganization by examining the relationship between demographic diversity and hate crime rates. This study focused on analyzing the relationship between the level of diversity, residential mobility, unemployment, family disruption, proximity to urban areas, and population density in all 21 New Jersey counties and hate crime rates. The existing data of Federal Bureau of Investigations' hate crime rates and the U.S. Census Bureau's demographic diversity, operationalized as the percentage of Whites over all other races, and social disorganization from 21 between the years 2007 through 2011, for a total sample size of 105 cases of reported hate crimes. Results of the multiple linear regression analysis indicate that ethnic diversity did not significantly predict hate crimes (p = 0.81), residential mobility (p < 0.001), and population density (p < 0.001) had positive effects on hate crime rates. Concentrated disadvantage (p = 0.01), characterized by the number of reported unemployment rates, had a negative effect on hate crime rates. The results of the study supported social disorganization theory in reference to residential mobility and population density. Law enforcement agencies can use the results of this study to combat hate crimes in areas with a high level of residential mobility and population density